PENGANGGARAN MODAL DALAM PENGAMBILAN KEPUTUSAN INVESTASI JANGKA PANJANG - Reza Zattira; Dhimas Jaka; Endri Purnomo (RELASI : JURNAL EKONOMI, 2016)
Significant lack of planning in making an investment by a company. This isbecause in planning an investment project certainly require substantial funds, so thatif it is not budgeted and calculated properly, it can result in the failure of investmentprojects that could cause a company suffered a great loss. This study discusses thecapital budgeting of a project in the CV. X will buy a corn seed drying machine. Inthis study is discussed in detail how to calculate the initial investments, estimatingrevenue to be obtained by the company when the project is, how long the capitalissued by the company to the investment project will be returned, and the mostimportant thing is feasible or not it is an investment project planning. The methodused in the calculation of capital budgeting is the payback period, discountedpayback period, Net Present Value (NPV), and Internal rate of Return (IRR). In thisstudy showed that planning the purchase of corn drying machine by CV X is receivedby calculating the payback period for 3 years 2 months 5 days, discounted paybackperiod 3 years 10 months 21 days, NPV > 0 or NPV positive and IRR > cost ofcapital, there is 21,70% > 10,80%.